INDIVIDUAL APPROACH TO DESIGN AND MANUFACTURE OF MOLDED LEATHER GOODS - BABYCH , АNTONINA; LYPSKI, TIMOFEY; RYBAK, KOSTYANTYN (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Relevance of the topic. Innovations, technologies, ecological notes in design, elements of new and unusual or vice versa elements of natural and usual are today a trend in the leather goods industry.Modular design of parts and assemblies, their formation when creating a rigid form attracts the attention of designers, fashion experts and practical specialists of the fashion industry and related specialists.Purpose of the study. The purpose of the study is to develop a collection of accessories from genuine leather in the style of ecological design with elements of molded rigid parts of the bag body in the form of a shell and its testing.The object of the study is the process of constructive shaping of the design and body of handbags from leather materials for the production of women's accessories.The subject of the study is a handbag with elements of rigid molded parts in the "eco" style.Research methods. The work used the observation method, the method of reviewing and analyzing data and literature, experimental methods for assessing the properties of materials and products by physical and mechanical indicators, as well as the method of determining the quality of products by experimental wearing.Elements of scientific novelty. For the first time in the industry, the method of forming leather materials on a plastic base using a previously created plaster cast to create rigid structures of handbags was used.Practical significance of the results of the work. A collage of inspiration, sketches and technical drawings of accessories, 3D models of bags were developed, a technology for casting an ingot and forming the frame of the product was developed. As a result, a collection of leather goods of the women's assortment "Ebb" in the form of a shell made in the conditions of the design studio "Kofta" and a package of design and technological documentation for the products were presented. The manufactured models were tested in laboratory conditions and approved during experimental wearing, which made it possible to confirm the high quality of the products, to affirm the successful combination of the functional and constructive component of the bag with the current aesthetic natural design.
Keywords: bag; form; plaster cast; technology; design; material; quality